The role of information in the credit relationship - Francesco Campanella; Manlio Del Giudice; Maria Rosaria Peruta (Journal of Innovation and Entrepreneurship, 2013)
A relationship between banks and firms that emphasizes the qualitative aspects of the enterprises may represent a response to the increasing difficulties of the credit system in financing a business system in which the intangible assets are the main source of value. In this view, an empirical survey on 61 bank managers of large and small banks has been carried out to verify the following: (1) the role of quantitative and qualitative information in the financing of large companies and small and medium enterprises and (2) how the relationship between bank and firm varies together with the dimensional change of the actors involved in the credit relationship.
Keywords: 650; relationship lending; soft information; hard information; Mann–Whitney test